ChemInform Abstract: Nickel‐Catalyzed Dimerization and Alkylarylation of 1, 3‐Dienes with Alkyl Fluorides and Aryl Grignard Reagents. Issue 36 (August 2016) - Iwasaki, Takanori; Min, Xin; Fukuoka, Asuka; Kuniyasu, Hitoshi; Kambe, Nobuaki
Abstract: Ni‐catalyzed dimerization of butadiene and subsequent alkylarylation reaction with arylmagnesium bromide and primary alkyl fluorides constitutes an efficient synthesis of 3‐alkyl‐8‐aryl‐1, 6‐octadienes.